Nymphs of the genus Isoperla Banks (Plecoptera, Perlodidae) from the Eastern Palaearctic Region - Teslenko, Valentina A.; Zhiltzova, Lidiya A. (Zootaxa, 2006)
The nymphs of the genus Isoperla Banks inhabiting the Eastern Palaearctic Region are reviewed. Previously unknown nymphs of Isoperla asiatica, I. eximia, I. flavescens, I. lunigera, I. maculata, I. mongolica, I. pseudornata are described and illustrated. A key is provided. Complementary distributional data are presented.